2013
DOI: 10.1007/s00044-013-0898-4
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted synthesis of some hybrid molecules containing penicillanic acid or cephalosporanic acid moieties and investigation of their biological activities

Abstract: Ethyl 4-amino-2-fluorophenylpiperazin-1-carboxylates containing a 1,3-oxazol(idin)e, 5-thioxo-1,2,4-triazole, 1,3,4-thiadiazole, 5-thioxo-1,3,4-oxadiazole, or 1,3-thiazole nucleus were obtained starting from ethyl piperazine-1-carboxylate (1) by several steps. The treatment of amine, 3 or hydrazide, 9 with several aromatic aldehydes generated the corresponding arylmethyleneamino (3a–f) or arylidenehydrazino (12a–c) compounds. The Mannich reaction between the 1,2,4-triazole or 1,3,4-oxadiazole compounds and 7-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In addition, in one of our previous studies the discovery of some azole compounds as antiurease agents served to merge the azole groups, namely 1,3‐oxazol(idin)e and 1,3‐thiazol(idin)e, with the penicillanic acid skeleton. Another reason for choosing these azole groups for hybridization is that some hybrid compounds carrying 1,3‐oxazol(idin)e or 1,3‐thiazol(idin)e nucleus were obtained as antilipase agents in our laboratory .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in one of our previous studies the discovery of some azole compounds as antiurease agents served to merge the azole groups, namely 1,3‐oxazol(idin)e and 1,3‐thiazol(idin)e, with the penicillanic acid skeleton. Another reason for choosing these azole groups for hybridization is that some hybrid compounds carrying 1,3‐oxazol(idin)e or 1,3‐thiazol(idin)e nucleus were obtained as antilipase agents in our laboratory .…”
Section: Resultsmentioning
confidence: 99%
“…Our research group has previously reported the synthesis of novel imine compounds, and most of these exhibited several biological activities including antimicrobial, antitumor, enzyme inhibition, and so on . As a part of our efforts aiming to obtain bioactive hybrid molecules, we performed the synthesis of arylidenehydrazides ( 5a , 5b , 5c , 5d , 5e ) via the condensation of compound 3 with suitable aldehydes.…”
Section: Resultsmentioning
confidence: 99%
“…Their applications in the treatment of inflammation, pain, migraine and asthma have also been reported. Some morpholine derivatives with antimicrobial activity have been synthesized in our laboratory …”
Section: Introductionmentioning
confidence: 99%